Rooftop Garden: An Initiative of Sovanagar High School - Hariswami Das; Suchandra Das; Somnath Chatterjee; Promod Jh (International Journal of Trends in Horticulture, 2024)
This paper examines the rooftop garden initiative at Sovanagar High School (HS), Malda, West Bengal, a project aimed at addressing a growing rural institution's environmental and educational needs. As the school's expansion reduced available green spaces, the administration sought an innovative solution that would restore greenery and serve as an educational resource. The rooftop garden integrates sustainable practices such as rainwater harvesting, vermicomposting, and the use of recycled materials, aligning with the broader goals of environmental education. The garden has been instrumental in enhancing the students' understanding of ecological and agricultural concepts by offering hands-on learning experiences that supplement their theoretical knowledge. Furthermore, the initiative contributes to the school's midday meal program, directly impacting students' nutrition. The project also extends beyond the school walls by engaging the local community, fostering a collaborative approach to environmental stewardship. Despite facing challenges such as the high installation cost and the need for specialized knowledge, the project has been largely successful. This success is evident in the improved environmental awareness among students, the reduction of the building's heat load, and the strengthening of the school's ties with the community. The rooftop garden at Sovanagar High School is a model for similar initiatives in rural settings, demonstrating that with careful planning and community involvement, schools can create multifunctional green spaces that contribute to education and sustainability. The paper concludes with recommendations for schools considering similar projects, emphasizing the importance of comprehensive planning, community engagement, and sustainable practices to ensure the long-term success of rooftop gardens.
Keywords: Environmental education; Rooftop garden; community engagement; rainwater harvesting; rural schools; sustainable practices; vermicomposting